Chapter The management of dredged materials: the «long and winding road» from waste to resource - LOLLI, ILARIA (Proceedings e report, 2020)
Both the dredging operations and the management of dredged materials may have heavy impacts on coastal and marine ecosystems. Dredged materials, in particular, have been considered for a very long time nothing more than a waste meant for disposal. Now the time has come to move from the 'disposal approach' to the 'waste recovery' or, even better, to the 'waste can be a non-waste' ones. Unfortunately, the management of dredged materials is committed to a congeries of rules, which build up a framework of law that appears plainly fragmentary and incoherent. The road is still long (and winding).